'Better Dressed than Birmingham'? Wholesale Clothing Catalogues and the Communication of Mass Fashion, 1920s to 1960s. (3rd May 2020) - Gilbert, Jenny
ABSTRACT: Birmingham's role in the mass-market fashion industry has been overlooked in scholarly accounts of the twentieth-century British clothing industry. London, Manchester and Leeds have all been the focus of studies from both business and fashion perspectives. This article examines the printed catalogues, branding and ephemera of four Birmingham wholesalers, highlighting the local and national significance of the city's clothing wholesale trade. Drawing upon Walsall Museum's Hodson Shop archive, documents in Birmingham Archives and Collections, and the University of Nottingham's Wholesale Textile Association (WTA) archive, this article outlines the companies that were referred to nationally as the Birmingham 'Big Four'. Wilkinson & Riddell, S. C. Larkins & Sons, Bell & Nicolson, and R. Lunt were located close together within the city centre. Whilst ostensibly competitors these companies worked together to protect their mutual interests and communicate the emerging idea of mass fashion to the region's shopkeepers, through print communications.